Changement organisationnel et reconception de l’organisation : des ressources aux capabilités - Justine Arnoud; Pierre Falzon (Activités)
This paper aims to describe the processes of organizational redesign-in-use as they are carried out by human operators following an organizational change. The purpose of these processes is to ensure production quality and to protect instances of cooperation which the structure, as it was designed, tends to ignore. The qualitative methodology we applied here allowed us to identify certain characteristics of the structure and to highlight the role of redesign processes. Our main results show that operators attempt to convert the organization’s resources into “capabilities”, i.e. into effective possibilities to “do the job” and “do the job well”. However, the rigid nature of the organization hinders such attempts, which are not always known or discussed within the organization. One goal of ergonomic intervention is therefore to provide evidence of these attempts and the means to discuss them, in order to implement a methodology which will support organizational redesign-in-use and to place human actors at the heart of organizational change.